Resolution of the online meeting of Russian experts on the EMPEROR-REDUCED trial - G. P. Arutyunov; A. G. Arutyunov; E. I. Tarlovskaya; A. S. Ametov; N. G. Vinogradova; A. A. Garganeeva; M. G. Glezer; I. V. Zhirov; M. V. Ilyin; N. A. Koziolova; A. O. Konradi; A. Yu. Lebedeva; et al. (Российский кардиологический журнал, 2020)
At the online meeting held on September 3, 2020, the results of the international multicenter trial EMPEROR-REDUCED were considered. Number of proposals and recommendations for the further study of cardiovascular and renal effects of empagliflozin and its practical use in heart failure patients were agreed.